Influence of Students’ Information Literacy Skills on the Perceived Image of Librarians in Nigerian Private Universities - Oso, Olutoyin Olukemi (Communicate: Journal of Library and Information Science, 2024)
This study examined the influence of students’ information literacy skills on the perceived image of librarians in private universities in South-west, Nigeria. Descriptive survey research design of the correlational type was adopted for this study. Total population of undergraduates in the six purposively selected private universities in South-west, Nigeria was 31,342. Sample size of 1,152 was selected from the population. The instrument used for data collection was Questionnaire was used as data collection instrument and was validated using face and content validity. Convenience sampling technique was used to administer questionnaire to undergraduates met physically utilising the library resources. Data gathered was analysed using descriptive and inferential statistics. The results revealed that there is a significant positive relationship between undergraduates’ level of information literacy skills and their perception about librarians’ image (r = 0.164, p = 0.01 < 0.05). The study recommended that librarians should continuously impart information literacy skills in undergraduate students by regularly organising specialised training programmes in order to bring about positive perception about librarians’ image. Also, librarians should be regularly equipped with on-the-job trainings and adequate facilities to enable them deliver quality services to users.